Ann Hui's Song of the exile - Yue, Audrey (New Hong Kong cinema., 2010)
In this work, Audrey Yue analyses a 1990 film considered by many to be one of Ann Hui's most haunting and poignant works, 'Song of the Exile'. Yue examines how Hui challenges the myth of the original home as singular, familial and romantic, and constructs the second home as a new space for Hong Kong modernity.